Retinal Oxalosis: Case Report and Review of Histopathology - Warwar, Ronald E.; Byun, Matthew; Bullock, John D.; Buerk, Bruce M. (Journal of Ocular Diseases and Therapeutics, 2014)
Oxalosis involves the deposition of calcium oxalate crystals throughout the body, including the eye and specifically the retina. Primary oxalosis involves an inborn metabolic defect in glyoxalate metabolism while secondary oxalosis occurs with excess oxalate ingestion, absorption, or acquired defects in its metabolism or excretion. Characteristic deposits are noted funduscopically, and crystal deposition primarily within retinal pigment epithelial cells ultimately leads to macular scarring and atrophy. Profound visual loss typically occurs as a result of advanced disease. Such findings are illustrated in the present case of a 27 year old woman with primary oxalosis.